2023
DOI: 10.1111/gcb.16739
|View full text |Cite
|
Sign up to set email alerts
|

Regional and global climate risks for reef corals: Incorporating species‐specific vulnerability and exposure to climate hazards

Abstract: Climate change is driving rapid and widespread erosion of the environmental conditions that formerly supported species persistence. Existing projections of climate change typically focus on forecasts of acute environmental anomalies and global extinction risks. The current projections also frequently consider all species within a broad taxonomic group together without differentiating species-specific patterns.Consequently, we still know little about the explicit dimensions of climate risk (i.e., species-specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 134 publications
0
4
0
Order By: Relevance
“…Yet, our findings emphasize that the winners and losers in coral assemblages exposed to more variable environments cannot be predicted using measures of long-term performance. Moreover, our observed heterogeneity in the short-term demographic characteristics of coral assemblages can help to explain why different assemblages display varying responses to periodic disturbances (Kim et al, 2023). This insight will benefit future predictions into the compositional reassembly of reef communities worldwide under future global change scenarios.…”
Section: Discussionmentioning
confidence: 74%
“…Yet, our findings emphasize that the winners and losers in coral assemblages exposed to more variable environments cannot be predicted using measures of long-term performance. Moreover, our observed heterogeneity in the short-term demographic characteristics of coral assemblages can help to explain why different assemblages display varying responses to periodic disturbances (Kim et al, 2023). This insight will benefit future predictions into the compositional reassembly of reef communities worldwide under future global change scenarios.…”
Section: Discussionmentioning
confidence: 74%
“…Kim et al [44] conducted a comprehensive study of 741 scleractinian coral species from various parts of the world. They found that coral reefs are under immense pressure and vulnerability worldwide.…”
Section: Impact Of Climate Change On Marine Biodiversitymentioning
confidence: 99%
“…The world's oceans have absorbed 93% of excess planetary heat from anthropogenic climate change ( Johnson and Lyman, 2020 ), threatening the survival of sessile marine organisms that cannot migrate to cooler climates to avoid increasingly frequent and severe marine heatwaves ( Atkins and Travis, 2010 ; Kim et al, 2023 ; Smith et al, 2023 ). Marine heatwaves have already decimated populations of keystone invertebrates, including notable losses of reef-building corals (scleractinians) ( Hughes et al, 2017 , 2018 ).…”
Section: Introductionmentioning
confidence: 99%